2012
DOI: 10.4161/cc.22387
|View full text |Cite
|
Sign up to set email alerts
|

The PERK-eIF2α phosphorylation arm is a pro-survival pathway of BCR-ABL signaling and confers resistance to imatinib treatment in chronic myeloid leukemia cells

Abstract: Activation of adaptive mechanisms plays a crucial role in cancer progression and drug resistance by allowing cell survival under stressful conditions. Therefore, inhibition of the adaptive response is considered as a prospective therapeutic strategy. The PERK-eIF2α phosphorylation pathway is an important arm of the unfolded protein response (UPR), which is induced under conditions of endoplasmic reticulum (ER) stress. Our previous work showed that ER stress is induced in chronic myeloid leukemia (CML) cells. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 47 publications
4
67
0
Order By: Relevance
“…10 Our previously shown data presented that TIAR, a known stress-responsive mRNA binding protein, binds to BRCA1 mRNA (Fig. 5) and is localized in the stress granules in CML cells (Fig.…”
Section: Bcr-abl1 Promotes Binding Of Hur and Tiar To Brca1 Mrna And mentioning
confidence: 83%
See 4 more Smart Citations
“…10 Our previously shown data presented that TIAR, a known stress-responsive mRNA binding protein, binds to BRCA1 mRNA (Fig. 5) and is localized in the stress granules in CML cells (Fig.…”
Section: Bcr-abl1 Promotes Binding Of Hur and Tiar To Brca1 Mrna And mentioning
confidence: 83%
“…9 In accordance to translation control, we showed that expression of BCR-ABL1 results in endoplasmic reticulum (ER) stress which leads to activation of unfolded protein response (UPR) and to phosphorylation of translation initiation factor 2 a subunit (eIF2a). 10 We found that this signaling cascade plays an essential role in imatinib resistance observed in CML cells. 10 Phosphorylation of eIF2a triggers TIA proteins action (TIA1/ TIAR), what briefly leads to rearrangement of cellular mRNA translation profile, thus protein synthesis profile in response to the cellular demand.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations